Hukum Pemakaian Sistem Pembayaran Shopee PayLater dalam Jual Beli Online Menurut Perspektif Fikih Muamalah - Andi Dahmayanti Muchtar; Syamsiah Nur; Miftahul Jannah (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2024)
Shopee PayLater is an online buying and selling system that is paid in installments with the terms and conditions applied by Shopee. This research aims to find out how muamalah jurisprudence reviews the payment system using Shopee PayLater. This research is a qualitative descriptive research (library research) with a normative juridical approach method. The results of research on Shopee PayLater contracts including qarḍ contracts, namely Shopee PayLater electronic money loans for e-commerce, show that these loans are not permitted because they contain elements that are contrary to Islamic law, namely the element of usury. The implication of this research is that all parties, especially Shopee users, should pay more attention to the contracts used in transactions so as not to fall into contracts that contain prohibited elements in the Shari'a.